Kajian keterampilan proses sains pada buku teks pelajaran fisika SMA kelas XII semester 1 - Azura Carolina Harsani; Desnita Desnita; Asrizal Asrizal; Yenni Darvina (Universitas Negeri Padang, 2020)
In the 2013 Physics Learning Curriculum is more emphasized on the Learning Process using the Process Skills approach to enhance students' Scientific Skills. based on observations in the field, it was found that the process skills had not been maximally performed. learning resources that become the main guidelines for teachers in Implementing Learning Activities are textbooks. however, the textbooks used in high schools in West Sumatra are very diverse, and it is not yet known which books can facilitate SPK. After the Survey, 4 books were used for a higher frequency, 3 of which were recommended by the government. This study aims to find out which books can facilitate the Implementation of Science Process Skills Presentation. Data was collected using an instrument analysis sheet, containing ten indicators of Science Process Skills (SPK), with 32 indicators. The instrument was validated by three experts obtained at the first expert with a score of 0.98% categorized as very valid, the second expert with a score of 0.96% categorized as very valid, and the third expert with a score of 0.85% categorized as very valid. The instrument was analyzed on the six main subjects, namely: Direct current electricity, Static electricity, Magnetic fields, Electromagnetic induction, Alternating current circuits, and Electromagnetic waves. The data collection technique used is the study of documents. Data analysis Techniques used Study content. The research results obtained that the books are used as a reference for Physics Learning in Class XII of Semester 1 High School which has the highest proportion of SPK Indicators, namely books by Writer Ketut Kamawijaya, Wawan.P with Grafindo Publishers in 2016, while books with the lowest proportion of Indicators Namely book by Author Sunardi, Paramitha Retno.P, Andreas B. Darmawan 2016.